PERAN KEPEMIMPINAN BU NYAI DALAM MEMANAJEMEN PESANTREN (STUDI KASUS PESANTREN AL-HIDAYAH PUTRI KARANG SUCI PURWOKERTO UTARA) - Khusnul Khotimah (Jurnal Penelitian Agama, 2017)
Abstract: Nyai's role in Pondok Pesantren al-Hidayah Putri Karang Suci includes the role of domestic leadership and the role of pulik leadership. The role of domestic leadership, among others; creating cleanliness and tidiness of the hut, creating discipline, instilling morality al-karimah on santri, and preparing the logistic needs of students. While the role of public leadership bu Nyai is planning, organizing, actuating and controlling. In the planning function, the thing that be done is to prepare the facilities and infrastructure of Islamic boarding school, designing activities of Islamic boarding school, preparing budget plans, preparing curriculum preparation. In the organizing function of the things done is organizing the board and boarding school, create a job description. In the actuating function, what is done is to direct and encourage the performance of subordinates in the implementation of daily and annual programs. In the controlling function, the thing that is done is to conduct direct and indirect evaluation. Another thing that is done by bu Nyai is equip facilities infrastructure, financing and doing cooperation. Keywords: The role of bu Nyai, Leadership, management, pesanten al-Hidayah Karang Suci Purwokerto